YouTube dan Panggung Komunikasi Politik: Media Klarifikasi Pemberitaan Negatif Media Massa Arus Utama - Tri Alida Apriliana, Tri Alida Apriliana (Jurnal Keamanan Nasional, 2021)
The presence of the internet and new media have provided opportunities for the public to participate in political conversations or debates through new media, which is user-generated content. New media of the user-generated content type is the media with content created by the users of the new media themselves. YouTube is a new type of media, although the interactions offered are not as busy as other social media, the use of YouTube is quite effective in boosting the popularity of political communicators. Through YouTube, important information can be disseminated in more personal or dialogical ways in responding to various public curiosity. During the last few years in Indonesia, Youtube has also been widely used by political communicators to upload videos containing political statements or attitudes on actual issue. It is often that Youtube is also used as a medium for political communicators to clarify when they feel that they have been described negatively by the mainstream mass media.